RELIGIOSITY AND RELIGIOUS STUDIES: CONTRIBUTION IN THE EMOTIONAL INTELLIGENCE OF UNIVERSITAS BINA BANGSA STUDENTS - Miftahudin, Miftahudin (LPPM Institut Pendidikan Nusantara Global, 2023)
This study discusses the role of religiosity and religious studies in contributing to the development of students' emotional intelligence. Religiosity and religious studies have long been important aspects of individual and societal life, and this study aims to understand its impact on students' emotional development. Through religious studies, students can develop a better emotional awareness of their own feelings and emotions, as well as recognize how those emotions affect behavior and interactions with others. The values of empathy, compassion, and responsibility instilled by religious practice also help students develop the ability to feel the feelings and perspectives of others, which are key aspects of emotional intelligence. In addition, religious practices provide guidance on how to cope with negative emotions and manage stress, thus helping students deal with challenges in a healthier and positive way. Religious studies also provide a deeper purpose in life and a sense of inspiration for students to achieve their goals, helping them stay energized in the face of obstacles, and seek deeper meaning in life. However, the positive effects of religiosity and religious studies on emotional intelligence can vary between individuals and depend on the application of religious values in daily life. Therefore, a holistic and inclusive approach in respecting the diversity of religious beliefs and religious practices is essential in recognizing the benefits of the role of religiosity and religious studies in shaping students who are more empathetic, balanced, and contribute positively to society.